2013
DOI: 10.1152/ajprenal.00504.2012
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of hepatocyte growth factor in the stenotic kidney

Abstract: Stewart N, Chade AR. Renoprotective effects of hepatocyte growth factor in the stenotic kidney. Am J Physiol Renal Physiol 304: F625-F633, 2013. First published December 26, 2012 doi:10.1152/ajprenal.00504.2012 damage and loss contribute to the progression of renal injury in renal artery stenosis (RAS). Hepatocyte growth factor (HGF) is a powerful angiogenic and antifibrotic cytokine that we showed to be decreased in the stenotic kidney. We hypothesized that renal HGF therapy will improve renal function mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…EVs are also rich in transcription factors involved in pro-angiogenic pathways, like HGF that stimulates proliferation and migration of endothelial and vascular smooth muscle cells 36, 37 . HES1 is a critical downstream effector of the Notch signaling pathway, and its activation regulates vascular remodeling and arterial fate of endothelial cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…EVs are also rich in transcription factors involved in pro-angiogenic pathways, like HGF that stimulates proliferation and migration of endothelial and vascular smooth muscle cells 36, 37 . HES1 is a critical downstream effector of the Notch signaling pathway, and its activation regulates vascular remodeling and arterial fate of endothelial cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in chronic renal disease with different etiologies have shown that renoprotective effects of experimental and clinically available drugs, such as antioxidants, 4 endothelin 5 or angiotensin receptor blockers, 6 and statins, 7 to name a few, are associated with a preservation of the renal microvasculature. Furthermore, therapeutic interventions using angiogenic cytokines 8,9 or progenitor cells, 10,11 which are known to have a primary effect on vascular proliferation, have also led to marked improvements in renal function and damage accompanied by recovery of the microvascular architecture, underscoring the potential of the renal microcirculation as a therapeutic target.…”
mentioning
confidence: 99%
“…Nowadays, recent instruments including microcomputed tomography permit the observation of tissue structures in three dimensions, which greatly facilitates visualization of the spatial distribution and connectivity of microvessels in organs including the kidney. This technique demonstrated improvements in the renal microvascular architecture after chronic ET A blockade in pigs with hypercholesterolemia [25] and in stenotic kidneys after infusion with hepatocyte growth factor [26]. Three-dimensional analysis has taught us that bidimensional observation no longer provides enough information on structural changes during the course of the disease or after pharmacological therapy.…”
Section: Resultsmentioning
confidence: 99%